Astrocyte specific chromatin accessibility differences in European vs African Alzheimer Disease brains. (20th December 2022) - Celis, Katrina; Griswold, Anthony J.; Rajabli, Farid; Whitehead, Patrice L.; Hamilton‐Nelson, Kara L.; Dykxhoorn, Derek M.; Nuytemans, Karen; Wang, Liyong; Weintraub, Sandra; Geula, Changiz; Gearing, Marla; Trojanowski, John Q; et al.
Abstract: Background: The APOE4 gene, the strongest genetic risk factor for late‐onset Alzheimer disease (AD), is highly expressed in astrocytes. The local ancestry (LA) region surrounding APOE4 (Chr19:44‐46Mb) is associated with increased AD risk for European (EU) compared to African (AF) APOE4 carriers. We previously demonstrated that APOE4 expression is higher in astrocytes from EU LA carrier brains using single nuclei RNA (snRNA) sequencing. We investigate whether chromatin accessibility differences could explain the APOE4 expression differences between ancestries. Method: We performed snRNA and assays for transposase accessible chromatin sequencing (snATAC) in six EU and six AF APOE4 AD brains. Bioinformatic analysis was performed using Seurat for snRNA and ArchR for snATAC. Result: 94, 411 and 60, 306 nuclei were sequenced by snRNA and snATAC, respectively. Following data integration, we resolved 11 distinct cell type clusters. We confirmed that APOE4 expression in astrocytes was higher in EU (Fold change=1.51; p =1.01x10 ‐113 ) and that chromatin accessibility is indeed higher in EU astrocytes at the APOE4 promoter and surrounding LA. Genome‐wide, astrocytes had the most differentially accessible peaks between ancestries (N=12, 518, 95% increased accessibility in EU) representing 2.1% of all peaks. Interestingly, chr19 had the most differentially accessible peaks between ancestries (N=964) with 98% increased accessibility in EU. (EU:245; AF:4) peaks were in the APOE4 LA region with 60% overlapping promoters. Pathway analysis of genes with increased chromatin accessibility in EU LA showed enrichment for lipoprotein assembly, remodeling, and clearance. Conclusion: This study represents initial efforts to investigate underlying mechanisms that contribute to the differential expression demonstrated between AF and EU LA brains surrounding APOE4 . Our results suggest that the increased EU APOE4 expression previously observed in EU AD LA APOE4 homozygotes relative to AF LA APOE4 homozygotes in astrocytes is at least partly due to increased EU astrocyte chromatin accessibility in the LA region.